Recentralization of Mining Licensing Authority and Its Impact on Local Autonomy in Indonesia - Hezron Sabar Rotua Tinambunan; Istislam; Shinta Hadiyantina; Adi Kusumaningrum; Amalina Ahmad Tajudin (Faculty of Law Universitas Negeri Surabaya, 2026)
Indexed by Scopus